Bioassays for TSH Receptor Autoantibodies, from FRTL-5 Cells to TSH Receptor–LH/CG Receptor Chimeras: The Contribution of Leonard D. Kohn - Giuliani, Cesidio; Saji, Motoyasu; Bucci, Ines; Napolitano, Giorgio (Frontiers in Endocrinology, 2016)
Since the discovery 60 years ago of the “long-acting thyroid stimulator” by Adams and Purves, great progress has been made in the detection of thyroid-stimulating hormone (TSH) receptor autoantibodies (TRAbs) in Graves’ disease. Today, commercial assays are available that can detect TRAbs with high accuracy and provide diagnostic and prognostic evaluation of patients with Graves’ disease. The present review focuses on the development of TRAbs bioassays, and particularly on the role that Leonard D. Kohn had in this. Indeed, 30 years ago, the Kohn group developed a bioassay based on the use of FRTL-5 cells that was characterized by high reproducibility, feasibility, and diagnostic accuracy. Using this FRTL-5 bioassay, Kohn and his colleagues were the first to develop monoclonal antibodies against the TSH receptor. Furthermore, they demonstrated the multifaceted functional nature of TRAbs in patients with Graves’ disease, with the identification of stimulating and blocking TRAbs, and even antibodies that activated pathways other than cAMP. After the cloning of the TSH receptor, the Kohn laboratory constructed human TSH receptor–rat luteinizing hormone/ chorionic gonadotropin receptor chimeras. This paved the way to a new bioassay based on the use of nonthyroid cells transfected with the Mc4 chimera. The new Mc4 bioassay is characterized by high diagnostic and prognostic accuracy, greater than for other assays. The availability of a commercial kit based on the Mc4 chimera is spreading the use of this assay worldwide, indicating its benefits for these patients with Graves’ disease. This review also describes the main contributions made by others researchers in TSH receptor molecular biology and TRAbs assay, especially with the development of highly potent monoclonal antibodies. A comparison of the diagnostic accuracies of the main TRAbs assays, as both immunoassays and bioassays, is also provided.